The followership styles of Malaysian National Primary School (NPS) deputy heads involved in the School Improvement Programme (SIP) - Mohd Ali, Hairuddin (2011)
The School Improvement Programme (SIP) is the central core strategy that the Ministry of Education Malaysia (MOEM) employs in fulfilling its educational mission. The purpose of this study is to examine the status of followership styles of the followers of NPS heads that involved in the SIP. The study selected 150 (out of 350) schools involved in MOEM’s SIP. Approximately 600 senior management team teachers were required to complete the 10-page survey questionnaire, which consists of 52 seven-point Likert scale items. The collection centre received 135 envelopes containing 420 completed survey questionnaires from the sampled schools towards the end of May 2007. The data screening process omitted 14 out of 420 cases prior to data analyses. The employment of a full fledge Structural Equation Modeling (SEM), AMOS 7.0 and SPSS statistical application would be used to confirm the dimensionality and the psychometric properties of the scales respectively. With the employment of a modified Kelly’s two-taxonomy followership styles, the study identified at least 88% of NPS heads in the SIP are followers from the pragmatist/survivor type. The findings from the study provide useful and pertinent information to senior management team teachers, the NPS heads and especially to MOEM as stakeholders. First, it will enable the senior management team members to reflect on themselves and thus try to shift their paradigm. This study is necessary, useful and relevant because it focuses on the status of the followership styles of the senior management teams of the schools of NPS heads in the SIP. The strong relationship between the two groups (and styles) will determine the future success of the schools involved. Hence, the success of these schools and SIP will ensure the success of MOEM’s mission.